Low cerebral blood flow after cardiac arrest is not associated with anaerobic cerebral metabolism. (November 2017) - Hoedemaekers, Cornelia W.; Ainslie, Philip N.; Hinssen, Stijn; Aries, Marcel J.; Bisschops, Laurens L.; Hofmeijer, Jeannette; van der Hoeven, Johannes G.
Abstract: Aim of the study: Estimation of cerebral anaerobic metabolism in survivors and non-survivors after cardiac arrest. Methods: We performed an observational study in twenty comatose patients after cardiac arrest and 19 healthy control subjects. We measured mean flow velocity in the middle cerebral artery (MFVMCA ) by transcranial Doppler. Arterial and jugular blood samples were used for calculation of the jugular venous-to-arterial CO2 /arterial to-jugular venous O2 content difference ratio. Results: After cardiac arrest, MFVMCA increased from 26.0[18.6–40.4] cm/sec on admission to 63.9[48.3–73.1] cm/sec after 72 h (p < 0.0001), with no significant differences between survivors and non-survivors (p = 0.4853). The MFVMCA in controls was 59.1[52.8–69.0] cm/sec. The oxygen extraction fraction (O2 EF) was 38.9[24.4–47.7]% on admission and decreased significantly to 17.3[12.1–26.2]% at 72 h (p < 0.0001). The decrease in O2 EF was more pronounced in non-survivors (p = 0.0173). O2 EF in the control group was 35.4[32.4–38.7]%. The jugular bulb-arterial CO2 to arterial-jugular bulb O2 content difference ratio was >1 at all time points after cardiac arrest and did not change during admission, with no differences between survivors and non-survivors. Values in cardiac arrest patients were similar to those in normal subjects. Conclusions: In this study, low CBF after cardiac arrest is not associated with anaerobic metabolism. Hypoperfusion appears to be the consequence of a decrease of neuronal functioning and metabolic needs. Alternatively, hypoperfusion may decrease cerebral metabolism. Subsequently, metabolism increases in survivors, consistent with resumption of neuronal activity, whereas in non-survivors lasting low metabolism reflects irreversible neuronal damage.